Suppose we are given

2x − 3

Let’s find its value for different value of x

####
**
For x = 1
**

2x − 3

= 2 × 1 − 3

= 2 − 3

= −1

####
**
For x = 2
**

2x −3

= 2 × 2 − 3

= 4 − 3

= 1

####
**
For x = 0
**

2x − 3

= 2 × 0 − 3

= 0 − 3

= −3

Similarly

##
For 10x
^{
2
}
− 10x + 10

####
**
For x = 1
**

10x
^{
2
}
− 10x + 10

= 10(1)
^{
2
}
− 10 (1) + 10

= 10 − 10 + 10

= 10

####
**
For x = 2
**

10x
^{
2
}
− 10x + 10

= 10(2)
^{
2
}
− 10(2) + 10

= 10 × 4 − 10 × 2 + 10

= 40 − 20 + 10

= 20 + 10

= 30